Temperature effects on carbon storage are controlled by soil stabilisation capacities - Iain P. Hartley (Nature Portfolio, 2021)
The extent to which temperature controls soil carbon storage remains highly uncertain. Here, the authors show that, globally, soil carbon stocks decline strongly with temperature, but the effect is much greater in coarse-textured soils with limited organic matter stabilisation capacities, than in fine-textured soils.